2016
DOI: 10.1371/journal.pntd.0005175
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Pathogenic Landscape of Helminth (Opisthorchis viverrini) Infections: A Cross-Sectional Study on Contributions of Physical and Social Environment and Healthcare Interventions

Abstract: BackgroundHelminth infections have proven recalcitrant to control by chemotherapy in many parts of Southeast Asia and indeed farther afield. This study isolates and examines the influence of different aspects of the physical and social environment, and uneven intervention effort contributing to the pathogenic landscape of human Opisthorchis viverrini infections.MethodologyA cross-sectional survey, involving 632 participants, was conducted in four villages in northeast Thailand to examine the impact on prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
(69 reference statements)
0
8
0
Order By: Relevance
“… 92 The level of precipitation, the change in flowing river and the man-made water reservoirs could also affect the habitat of fishes and snails, which could inevitably affect the prevalence of liver fluke. 93 , 94 …”
Section: Future Trendmentioning
confidence: 99%
“… 92 The level of precipitation, the change in flowing river and the man-made water reservoirs could also affect the habitat of fishes and snails, which could inevitably affect the prevalence of liver fluke. 93 , 94 …”
Section: Future Trendmentioning
confidence: 99%
“…A cross-sectional study in Thailand found that prioritization of the parasite Opisthorchis viverrini by village-level health centers had an impact on risk of infection (Ong et al, 2016). Although, interestingly, behavior regarding consumption of raw fish did not have a significant impact on risk of infection, the authors emphasize the need for a holistic approach in considering control measures for this pathogen, particularly consideration of those factors that constitute the broader pathogenic landscape (Ong et al, 2016).…”
Section: Parasite-specific Interventions: Opisthorchis Sppmentioning
confidence: 99%
“…The differences in prevalence between the districts maybe due to their respective distance to the waterbodies where communities procure fish for consumption. A study by Ong et al (2016) has shown that the distance to waterbody had an impact on how villagers source the fish used in raw fish dishes. Differences in the infections levels in fish are also dependent on the waterbody, thus can affect the risk of human exposure to the infections (Ong et al, 2016).…”
Section: Study Population and Prevalencementioning
confidence: 99%
“…A study by Ong et al (2016) has shown that the distance to waterbody had an impact on how villagers source the fish used in raw fish dishes. Differences in the infections levels in fish are also dependent on the waterbody, thus can affect the risk of human exposure to the infections (Ong et al, 2016). Compare to That Phanom and Na Kae, Wang Yang district is located within the waterway of the Nam Kam River which flows from the neighbouring province of Sakon Nakhon toward downstream of the Mekong River.…”
Section: Study Population and Prevalencementioning
confidence: 99%